Dental caries and periodontal disease among people who use drugs: a systematic review and meta-analysis - Mohsen Yazdanian; Bahram Armoon; Alireza Noroozi; Rasool Mohammadi; Amir-Hosein Bayat; Elahe Ahounbar; Peter Higgs; Hormoz Sanaei Nasab; Azadeh Bayani; Morteza Hemmat (BMC, 2020)
Abstract Background The aim of our study was to perform a systematic review of the literature and meta-analysis in order to investigate relationship between drug use and oral health. Methods We searched for studies in English published before July 1, 2019 on PsycINFO, PubMed, SciELO, Scopus, and Web of Science. We assessed the relationship between drug use (methamphetamines, heroin; opiates; crack, cocaine and cannabis as dependent variables) and reported tooth loss, periodontal disease, or decayed, missing, and filled teeth index as an independent variable. The data were analyzed using Stata 12.0 software. Results We initially identified 1836 potential articles (with 1100 duplicates) and screened the remaining 736 titles and abstracts, comprising 54 studies. In the next step, we evaluated the full-texts; 44 studies were excluded, accordingly. In total, we included 10 publications in the meta-analysis. Drug type was associated with periodontal disease (OR 1.44; 95% CI 0.8-2.6) and pooled estimates showed that type of drug used increased the odds of the number of decayed, missed and filled teeth (DMFT) (OR 4.11; 95% CI 2.07-8.15) respectively. Conclusions The analytical challenges of segregating the impact of individual drug types on oral health diseases mean that investigations on the direct relationship between oral health status and drug use are limited. Developing programs to improve potential confounding with various substances and addressing the dental health needs of people who use drugs is vital if we are to improve their overall quality of life.